'Transforming' children's services? : social work, neoliberalism and the "Modern" world - Garrett, Paul Michael , 1958- (Open University Press, 2009)
Transforming Children's Services will be a vital text for social work and social policy students. Furthermore, the book directly addresses a range of issues of direct concern to practitioners